Ocular involvement in monkeypox: Description of an unusual presentation during the current outbreak. Issue 5 (November 2022) - Mazzotta, V; Mondi, A; Carletti, F; Baldini, F; Santoro, R; Meschi, S; Moccione, M; Gebremeskel Teklè, S; Minosse, C; Camici, M; Vita, S; Matusali, G; et al.
Highlights: In the current multinational outbreak of MPX, ocular complications have been reported very rarely compared with what has been reported in previous outbreaks in endemic settings. This is one of the first cases described of monkeypox (MPX) with ocular involvement with an infective and replication competent MPXV isolated in culture. The time-course of the ocular manifestations (ocular onset delayed with respect to the skin rash and concomitant systemic symptoms).is suggestive of a pathogenetic mechanism based on self-inoculation from skin lesions. Viral clearance and clinical recovery after treatment with intravenous Cidofovir were slow.